Myocardial Infarction Elevates Inflammation and Contributes to the Formation of Atheroma Plaques in the Aorta of Hypercholesterolaemic Rats - Kurniati, Neng F; Angelia, Teresa; Artarini, Aluicia A; Nurfatwa, Maritsa (UI Scholars Hub, 2018)
Background: Myocardial infarction (MI) is the clinical manifestation of coronary heart disease that can be caused by athesclerotic plaque rupture. However, the role of MI in influencing endothelial cells is still not clearly known, especially in atheroma plaque development. The aim of this study was to determine the effect of MI in the inflammatory processes occurring in the hypercholesterolaemic rat aorta and heart by measuring myeloperoxidase (MPO) levels. Methods: Wistar rats were categorised into normal, normal–MI, hypercholesterolaemic and hypercholesterolaemic–MI groups. Hypercholesterolaemia was induced in rats by feeding them with a high-cholesterol diet, followed by oral administrations of cholesterol, cholic acid and propylthiouracil. The MI rat model was created by injecting isoproterenol (intraperitoneal) 1 day before the animals were sacrificed. The success of the induction was confirmed based on a significant increase in total cholesterol values compared to those in the normal group. The inflammatory condition was determined by measuring the MPO levels using the dot blot method. Results: MPO expression was increased significantly in the hypercholesterolaemic rats compared to that in the normal group. The highest aorta MPO expression was observed in the hypercholesterolaemic–MI group. Both MI rats and hypercholesterolaemic rats showed a similar increase in MPO expression in the heart (71.7% and 75.5%, respectively). However, the hypercholesterolaemic–MI rats showed the highest MPO expression (119.59%). Conclusions: MI accelerates inflammation in the aorta of hyper-cholesterolaemic rats.